Hollow aluminum-doped lithium manganate and method of preparation and use thereof
Patent Information
- Application Number
- CN202410100338.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-01-24
AI Technical Summary
Existing spinel-type manganese oxides have low actual lithium extraction capacity in the process of lithium extraction from salt lakes, and it is necessary to improve the stability and lithium extraction capacity of the materials.
Using alumina as a template agent, alumina particles are coated with manganese carbonate to form a mesoporous structure. The alumina is then etched by alkaline treatment to retain some aluminum elements, thus achieving aluminum doping and preparing hollow spherical aluminum-doped lithium manganese oxide.
It increases the specific surface area of lithium-ion sieve materials, reduces lithium-ion diffusion distance, enhances lithium extraction rate and capacity, stabilizes material structure, and improves electrochemical stability.
Smart Images

Figure CN117936739B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium extraction technology, and relates to a hollow aluminum-doped lithium manganese oxide, its preparation method and uses. Background Technology
[0002] Lithium and its compounds have broad application prospects. With the rapid and large-scale development of lithium-ion energy storage, such as power batteries, the demand for lithium resources is increasing. Lithium extraction technology refers to the techniques for extracting lithium from various lithium-containing ores or salt lakes. Currently, there are various lithium extraction technologies, including potassium sulfate method, spodumene lithium extraction, mica lithium extraction, clay lithium extraction, brine lithium extraction, lithium-ion sieve adsorption lithium extraction, and electrochemical deintercalation method for salt lake lithium extraction, etc.
[0003] Electrochemical lithium extraction technology, especially methods for directly extracting lithium from salt lake brine, offers high extraction rates and low costs. A key aspect of this technology lies in the selection of electrode materials. Developing or selecting electrode materials capable of efficiently extracting lithium, improving their stability and cycle life, reducing energy consumption during extraction, and minimizing the impact of impurity ions are crucial.
[0004] Lithium-ion sieve materials are materials that can selectively identify and adsorb lithium ions. They are based on the mechanism of ion exchange, that is, after the target lithium ions are extracted (lithium-poor state), they can be reintroduced and reacted to form a composite material (lithium-rich state). Therefore, they can be used in electrochemical lithium extraction technology, such as titanate lithium-ion sieves (e.g., lithium titanate), phosphate lithium-ion sieves (e.g., lithium iron phosphate), and silicate lithium-ion sieves (e.g., lithium silicate). However, none of the above types of lithium-ion sieves can simultaneously have high lithium extraction capacity and long-term stability.
[0005] Spinel-type manganese oxides are a recently popular lithium-ion sieve material. Their stable spinel structure and unique three-dimensional tunnel structure give them advantages such as high adsorption capacity, good selectivity, good recyclability, and low raw material cost, making them an ideal electrochemical adsorption material. Currently, spinel-type manganese oxides used for lithium extraction from salt lakes include MnO2·0.5H2O, λ-MnO2, and MnO2·0.3H2O, with adsorption capacities of 72.33 mg·g⁻¹, respectively. -1 39.68 mg·g -1 58.76 mg·g -1 The theoretical lithium extraction capacity corresponds to Li in the lithium-rich state. 1.6 Mn 1.6 O4, LiMn2O4, Li4Mn5O 12 Precursor materials.
[0006] However, the actual lithium extraction capacity of MnO2·0.5H2O in the existing technology only reaches 20-30 mg·g. -1Therefore, it is necessary to treat MnO2·0.5H2O and Li 1.6 Mn 1.6 Research and development of O4 are being conducted to optimize and improve its actual lithium extraction capacity and other performance characteristics. Therefore, this is of great significance for the efficient extraction of high-reserved, low-grade (concentrated) seawater / brine lithium resources. Summary of the Invention
[0007] In view of the problems existing in the prior art, the purpose of this invention is to provide a hollow aluminum-doped lithium manganese oxide, its preparation method, and its uses. The preparation method involves obtaining manganese carbonate-coated alumina particles, first calcining and decomposing a portion of the manganese carbonate to form a mesoporous structure, then etching the alumina through alkali treatment to retain some aluminum elements while creating the hollow structure. Aluminum doping is then achieved during the calcination and decomposition of the remaining manganese carbonate, ultimately yielding hollow spherical aluminum-doped lithium manganese oxide. The hollow spherical structure and mesoporous structure give the material a high specific surface area, effectively reducing the lithium-ion diffusion distance, increasing the lithium-ion storage space, and thus improving the lithium extraction rate and capacity. It also buffers local volume changes in the material, reducing polarization, thereby stabilizing the material structure and improving electrochemical stability.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a method for preparing hollow aluminum-doped lithium manganese oxide, the method comprising:
[0010] Alumina, manganese salt and carbonate are mixed to obtain manganese carbonate coated alumina particles;
[0011] The manganese carbonate-coated alumina particles are subjected to a first calcination to decompose part of the manganese carbonate, resulting in manganese carbonate / manganese oxide-coated alumina particles with porous surfaces.
[0012] The manganese carbonate / manganese oxide-coated alumina particles are subjected to alkali treatment to obtain the first hollow sphere;
[0013] The first hollow sphere is subjected to a second calcination to decompose the remaining manganese carbonate, thereby obtaining the second hollow sphere;
[0014] The second hollow sphere is mixed with a lithium source and then subjected to a third calcination to obtain hollow aluminum-doped lithium manganese oxide.
[0015] The preparation method of this invention uses alumina as a template agent to coat manganese carbonate onto alumina particles. A first calcination is then performed to partially decompose the manganese carbonate into manganese oxide. The CO2 emitted during the decomposition process creates pores on the surface. These mesoporous structures allow a small amount of aluminum hydroxide produced during subsequent alkaline treatment to remain in the first hollow sphere. Therefore, the first hollow sphere is an alumina particle coated with a mixture of manganese carbonate and manganese oxide (Mn2O3). When the alumina is etched and a second calcination is performed, the remaining manganese carbonate completely decomposes and is in-situ doped with the retained aluminum element. Therefore, the second hollow sphere is a composite of manganese oxide and aluminum oxide. Finally, it is mixed with a lithium source and subjected to a third calcination to synthesize aluminum-doped lithium manganese oxide in a solid-state process.
[0016] Compared to existing technologies that use solid manganese carbonate to prepare hollow manganese oxide, the lithium manganese oxide obtained in this invention undergoes in-situ aluminum doping. Aluminum doping can effectively improve the stability of the spinel lithium manganese oxide lattice, reduce manganese capacity loss, and thus improve cycle stability. Furthermore, this invention first prepares surface-porous manganese carbonate / manganese oxide, and after a series of alkaline hydrolysis, calcination oxidation, and solid-state synthesis, obtains more mesoporous structures, which can increase the specific surface area of the material, reduce the distance of lithium ion diffusion, increase the lithium ion storage space, and thus improve the lithium extraction rate and lithium extraction capacity. It can also buffer local volume changes in the material and reduce polarization, thereby stabilizing the material structure and improving electrochemical stability.
[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following technical solutions.
[0018] As a preferred embodiment of the present invention, the alumina is a micron-sized powder.
[0019] Preferably, the average particle size of the alumina is 1 to 4 μm, such as 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm or 4 μm, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0020] As a preferred technical solution of the present invention, the method for mixing alumina, manganese salt and carbonate includes: dispersing alumina in water, adding manganese salt and dissolving it, ultrasonically mixing for 0.5 to 2 hours, for example 0.5 hours, 0.8 hours, 1 hour, 1.5 hours or 2 hours, adding carbonate dropwise and dissolving it, stirring and reacting for 0.5 to 2 hours, for example 0.5 hours, 0.8 hours, 1 hour, 1.5 hours or 2 hours, then aging for 8 to 16 hours, for example 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, and then centrifuging, washing and drying to obtain manganese carbonate-coated alumina particles; however, it is not limited to the values listed, and other unlisted values within the above range are also applicable.
[0021] Preferably, the amount of manganese salt used is controlled according to the concentration of manganese salt being 1 to 1.5 mol / L, such as 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, or 1.5 mol / L, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0022] Preferably, the mass ratio of the alumina, manganese salt, and carbonate is (0.5-1):1.1:1, for example, 0.5:1.1:1, 0.6:1.1:1, 0.7:1.1:1, 0.8:1.1:1, 0.9:1.1:1, or 1:1.1:1, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0023] Preferably, both the manganese salt and the carbonate are soluble salts.
[0024] Preferably, the manganese salt includes at least one of manganese chloride, manganese nitrate, manganese acetate, or manganese sulfate. Typical but non-limiting combinations include combinations of manganese chloride and manganese nitrate, manganese chloride and manganese acetate, manganese chloride and manganese sulfate, manganese nitrate and manganese acetate, manganese nitrate and manganese sulfate, or manganese acetate and manganese sulfate, etc.
[0025] Preferably, the carbonate includes at least one of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, or ammonium bicarbonate. Typical but non-limiting combinations include combinations of sodium carbonate and sodium bicarbonate, sodium carbonate and potassium carbonate, sodium carbonate and potassium bicarbonate, sodium carbonate and ammonium bicarbonate, potassium carbonate and potassium bicarbonate, or potassium bicarbonate and ammonium bicarbonate.
[0026] As a preferred embodiment of the present invention, the heating rate of the first calcination is 1 to 5°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, etc., the holding temperature is 200 to 300°C, such as 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, etc., and the time is 2 to 3 hours, such as 2 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3 hours, etc., but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0027] Understandably, the first calcination only decomposes part of the manganese carbonate, so its calcination temperature is relatively low, while the second calcination needs to decompose both the manganese carbonate and manganese carbonate completely, so it should be at a higher temperature.
[0028] As a preferred embodiment of the present invention, the alkaline solution used in the alkaline treatment includes sodium hydroxide or potassium hydroxide.
[0029] Preferably, the pH of the alkaline solution used for the alkaline treatment is 9 to 12, such as 9, 9.5, 10, 10.5, 11, 11.5 or 12, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0030] Preferably, the alkali treatment time is 0.5 to 1 hour, such as 0.5 hours, 0.6 hours, 0.7 hours, 0.8 hours, 0.9 hours, or 1 hour, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0031] As a preferred embodiment of the present invention, the heating rate of the second calcination is 1 to 5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 5°C / min, etc., the holding temperature is 500 to 800°C, for example, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, or 800°C, etc., and the time is 4 to 6 hours, for example, 4 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours, 5 hours, 5.2 hours, 5.4 hours, 5.6 hours, 5.8 hours, or 6 hours, etc., but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0032] As a preferred embodiment of the present invention, the lithium source includes lithium hydroxide.
[0033] Preferably, the method for mixing the second hollow sphere with the lithium source includes: grinding until there are no obvious particles.
[0034] Preferably, the mass ratio of the second hollow sphere to the lithium source is 1:(2~2.2), such as 1:2, 1:2.02, 1:2.04, 1:2.06, 1:2.08, 1:2.1, 1:2.12, 1:2.14, 1:2.16, 1:2.18 or 1:2.2, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0035] Preferably, the third calcination includes calcination at a first temperature and then calcination at a second temperature.
[0036] It should be noted that the purpose of the third calcination stage is to generate the target spinel lithium manganese oxide from the hollow spheres and lithium source. During the third calcination process, after the first calcination at the first temperature, LiAl will be generated first. x Mn 1-x O2, after being calcined at a second, higher temperature, transforms into L. 1.6 Al y Mn 1.6-y O4.
[0037] Preferably, the first temperature is 100-140℃, such as 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃ or 140℃, and the calcination time at the first temperature is 24-72h, such as 24h, 30h, 36h, 42h, 48h, 54h, 60h, 66h or 72h, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0038] Preferably, the second temperature is 400-600℃, such as 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃, 540℃, 560℃, 580℃, 600℃, 620℃, 640℃, 660℃, 680℃, or 700℃, etc., and the calcination time at the second temperature is 2-6 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, or 6 hours, etc., but it is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0039] Preferably, the heating rate of the third calcination is 1 to 5 °C / min, such as 1 °C / min, 2 °C / min, 3 °C / min, 5 °C / min, etc., but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0040] In a second aspect, the present invention provides a hollow aluminum-doped lithium manganese oxide, which is obtained using the preparation method described in the first aspect;
[0041] Preferably, the hollow aluminum-doped lithium manganese oxide comprises LiAl x Mn 1-x O2 and / or L 1.6 Al y Mn 1.6-y O4, 0 < x < 1, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc., 0 < y < 1.6, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5 or 1.6, etc., but not limited to the listed values, other unlisted values within the above range also apply.
[0042] Thirdly, the present invention provides a lithium extraction and deintercalation electrode, wherein the lithium extraction and deintercalation electrode contains the hollow aluminum-doped lithium manganese oxide described in the second aspect.
[0043] It should be noted that when the hollow aluminum-doped lithium manganese oxide obtained by this invention is used as an electrode material in the field of lithium extraction, it should be subjected to appropriate delithiation treatment, such as acid treatment, to transform the hollow aluminum-doped lithium manganese oxide into a lithium-poor state so that it can be used as a lithium ion sieve for lithium extraction.
[0044] Thirdly, the present invention provides a lithium extraction apparatus, the lithium extraction apparatus comprising the lithium extraction and deintercalation electrode described in the second aspect.
[0045] Compared with existing technical solutions, the present invention has at least the following beneficial effects:
[0046] The preparation method of this invention uses alumina as a template agent and dopant source. Alumina particles are coated with manganese carbonate. First, some of the manganese carbonate is calcined and decomposed to form a small number of surface pores. Then, the alumina is etched by alkali treatment to retain some aluminum while creating a hollow structure. Aluminum doping is then achieved during the calcination and decomposition of the remaining manganese carbonate, ultimately yielding hollow, spherical aluminum-doped lithium manganese oxide. Aluminum doping effectively improves the stability of the spinel lithium manganese oxide lattice, reduces manganese capacity loss, and thus improves cycle stability. Simultaneously, through microstructure optimization, the formation of hollow spherical and mesoporous structures gives the material a high specific surface area, effectively reducing the lithium-ion diffusion distance, increasing lithium-ion storage space, and thus improving the lithium extraction rate and capacity. It also buffers local volume changes in the material, reducing polarization, thereby stabilizing the material structure and improving electrochemical stability. Attached Figure Description
[0047] Figure 1Here is a SEM image of lithium manganese oxide obtained in Example 1;
[0048] Figure 2 SEM image of lithium manganese oxide obtained in Comparative Example 1;
[0049] Figure 3 The XRD patterns of lithium manganese oxide obtained in Example 1 and Comparative Example 1 are shown below.
[0050] Figure 4 XPS test images of lithium manganese oxide obtained in Example 1, Comparative Example 1 and Example 5;
[0051] Figure 5 The BET test results are for lithium manganese oxide obtained in Example 1 and Comparative Example 1. Detailed Implementation
[0052] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0053] Those skilled in the art will understand that the embodiments described are merely illustrative of the invention and should not be construed as limiting the invention.
[0054] Example 1
[0055] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide, the method comprising:
[0056] (1) Disperse micron-sized alumina (average particle size of 2 μm) in deionized water, add manganese chloride to make the concentration of manganese chloride in deionized water 1.5 mol / L, ultrasonically mix for 1 h, then add sodium bicarbonate dropwise, controlling the mass ratio of the micron-sized alumina, manganese chloride and sodium bicarbonate to 1:1.1:1, stir and react for 1 h after the addition is complete, then let stand and age for 12 h, centrifuge, wash three times with deionized water, and vacuum dry at 80 °C for 24 h to obtain manganese carbonate coated alumina particles;
[0057] (2) The manganese carbonate-coated alumina particles were placed in a muffle furnace and heated to 200°C at a heating rate of 5°C / min for a first calcination of 2h to decompose part of the manganese carbonate and obtain manganese carbonate / manganese oxide-coated alumina particles with mesoporous structure.
[0058] (3) The manganese carbonate / manganese oxide coated alumina particles were redispersed in a strong alkaline solution (sodium hydroxide aqueous solution with pH = 9.2), stirred for 0.5 h to etch the alumina, then centrifuged, washed three times with deionized water, and vacuum dried at 80℃ for 24 h to obtain the first hollow sphere.
[0059] (4) The first hollow sphere is placed in a muffle furnace and heated to 800°C at a heating rate of 5°C / min for a second calcination for 5 hours to decompose the remaining manganese carbonate and obtain the second hollow sphere.
[0060] (5) The second hollow sphere was mixed with lithium hydroxide monohydrate at a mass ratio of 1:2 and ground in an agate mortar until no obvious particles were felt. The mixture was then transferred to an autoclave and heated at a first temperature of 120°C for 48 hours to obtain LiAl. x Mn 1-x O2 was further heated to a second temperature of 600℃ at a rate of 5℃ / min and calcined for 4 hours to obtain L. 1.6 Al y Mn 1.6-y O4, denoted as LAMO.
[0061] Example 2
[0062] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide, the method comprising:
[0063] (1) Disperse micron-sized alumina (average particle size of 1 μm) in deionized water, add manganese acetate to make the concentration of manganese acetate in deionized water 1 mol / L, ultrasonically mix for 1 h, then add sodium carbonate dropwise, control the mass ratio of micron-sized alumina, manganese acetate and sodium carbonate to be 0.8:1.1:1, stir and react for 1 h after the addition is complete, then let stand and age for 12 h, centrifuge, wash three times with deionized water, and vacuum dry at 80 °C for 24 h to obtain manganese carbonate coated alumina particles;
[0064] (2) The manganese carbonate-coated alumina particles were placed in a muffle furnace and heated to 300°C at a heating rate of 5°C / min for a first calcination of 2h to decompose part of the manganese carbonate and obtain manganese carbonate / manganese oxide-coated alumina particles with mesoporous structure.
[0065] (3) The manganese carbonate / manganese oxide coated alumina particles were redispersed in a strong alkaline solution (sodium hydroxide aqueous solution with pH = 10.2), stirred for 1 h to etch the alumina, then centrifuged, washed three times with deionized water, and vacuum dried at 80℃ for 24 h to obtain the first hollow sphere.
[0066] (4) The first hollow sphere is placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min for a second calcination for 5 hours to decompose the remaining manganese carbonate and obtain the second hollow sphere.
[0067] (5) The second hollow sphere was mixed with lithium hydroxide monohydrate at a mass ratio of 1:2.2 and ground in an agate mortar until no obvious particles were felt. The mixture was then transferred to an autoclave and heated at a first temperature of 120°C for 48 hours to obtain LiAl.x Mn 1-x O2 was further heated to a second temperature of 400℃ at a rate of 5℃ / min and calcined for 4 hours to obtain L. 1.6 Al y Mn 1.6-y O4, denoted as LAMO.
[0068] Example 3
[0069] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide, the method comprising:
[0070] (1) Disperse micron-sized alumina (average particle size of 3.5 μm) in deionized water, add manganese sulfate to make the concentration of manganese sulfate in deionized water 1.3 mol / L, ultrasonically mix for 1 h, then add ammonium bicarbonate dropwise, controlling the mass ratio of micron-sized alumina, manganese sulfate and ammonium bicarbonate to be 0.8:1.1:1, stir and react for 1 h after the addition is complete, then let stand and age for 12 h, centrifuge, wash three times with deionized water, and vacuum dry at 80 °C for 24 h to obtain manganese carbonate coated alumina particles;
[0071] (2) The manganese carbonate-coated alumina particles were placed in a muffle furnace and heated to 200°C at a heating rate of 5°C / min for a first calcination of 3h to decompose part of the manganese carbonate and obtain manganese carbonate / manganese oxide-coated alumina particles with mesoporous structure.
[0072] (3) The manganese carbonate / manganese oxide coated alumina particles were redispersed in a strong alkaline solution (potassium hydroxide aqueous solution with pH = 11.7), stirred for 1 h to etch the alumina, then centrifuged, washed three times with deionized water, and vacuum dried at 80℃ for 24 h to obtain the first hollow sphere.
[0073] (4) The first hollow sphere is placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min for a second calcination for 5 hours to decompose the remaining manganese carbonate and obtain the second hollow sphere.
[0074] (5) The second hollow sphere was mixed with lithium hydroxide monohydrate at a mass ratio of 1:2.1 and ground in an agate mortar until no obvious particles were felt. The mixture was then transferred to an autoclave and heated at a first temperature of 120°C for 48 hours to obtain LiAl. x Mn 1-x O2 was further heated to a second temperature of 600℃ at a rate of 5℃ / min and calcined for 4 hours to obtain L. 1.6 Al y Mn 1.6-y O4, denoted as LAMO.
[0075] Example 4
[0076] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (1), the mass ratio of micron-sized alumina, manganese chloride and sodium bicarbonate is adjusted from 1:1.1:1 to 0.2:1.1:1. Except for the above, the other conditions are exactly the same as in Example 1.
[0077] Example 5
[0078] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (1), the mass ratio of micron-sized alumina, manganese chloride and sodium bicarbonate is adjusted from 1:1.1:1 to 0.5:1.1:1. Except for the above, the other conditions are exactly the same as in Example 1.
[0079] Example 6
[0080] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (1), the mass ratio of micron-sized alumina, manganese chloride and sodium bicarbonate is adjusted from 1:1.1:1 to 0.8:1.1:1. Except for the above, the other conditions are exactly the same as in Example 1.
[0081] Example 7
[0082] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (1), the mass ratio of micron-sized alumina, manganese chloride and sodium bicarbonate is adjusted from 1:1.1:1 to 1.3:1.1:1. Except for the above, the other conditions are exactly the same as in Example 1.
[0083] Example 8
[0084] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (2), the temperature of the first calcination is adjusted from 200°C to 150°C. Except for the above, the other conditions are exactly the same as in Example 1.
[0085] Example 9
[0086] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (2), the temperature of the first calcination is adjusted from 200°C to 300°C. Except for the above, the other conditions are exactly the same as in Example 1.
[0087] Example 10
[0088] This embodiment provides a method for preparing hollow aluminum-doped lithium manganese oxide. In step (2), the temperature of the first calcination is adjusted from 200°C to 400°C. Except for the above, the other conditions are exactly the same as in Example 1.
[0089] Comparative Example 1
[0090] This comparative example provides a method for preparing lithium manganese oxide, the method comprising:
[0091] Manganese sulfate was dissolved in deionized water (concentration 0.02 mol / L) and 1 / 5 volume of ethanol was added as a dispersant to obtain solution A. 2.0 g of ammonium bicarbonate was dissolved in 200 mL of deionized water (concentration 0.2 mol / L) to obtain solution B. Solutions A and B were mixed and allowed to stand for 12 h. The mixture was then vacuum filtered, washed twice each with deionized water and anhydrous ethanol, and dried under vacuum at 80 °C for 24 h to obtain a pink powder, which was identified as nano-MnCO3 powder. The average particle size was measured to be 1.2 μm using a DSL filter.
[0092] The obtained light pink spherical MnCO3 powder precursor was placed in a muffle furnace and pre-sintered at 300℃ for 3h at a heating rate of 2℃ / min to achieve partial decomposition of the surface of MnCO3 microspheres. Then, the pre-sintered sample was acid-washed with 0.1M HCl solution for 2 days to remove the undecomposed MnCO3 inside. After filtration, it was washed with deionized water until neutral and vacuum dried at 100℃ for 12h to obtain hollow MnO2 microspheres. These microspheres were then calcined in a muffle furnace at 800℃ for 5h to obtain hollow Mn2O3.
[0093] Mn2O3, lithium hydroxide monohydrate, and aluminum oxide were ground in an agate mortar with a Li:Mn:Al molar ratio of 1.2:1:0.3 until no obvious particles were felt. The mixture was then transferred to an autoclave and heated at 120°C for 48 hours. The temperature was then further increased to 600°C and calcined for 4 hours to obtain LAMO.
[0094] (1) The microstructure of the material was observed using a JEOL JSM-6490LV scanning electron microscope. Figure 1 Here is a SEM image of lithium manganese oxide obtained in Example 1; Figure 2 The image shows a SEM image of the lithium manganese oxide obtained in Comparative Example 1. As can be seen from the image, the material prepared in Example 1 has more pores on its surface and also has a hollow structure.
[0095] (2) The crystal phase and crystal structure of the material were studied using an X-ray powder diffractometer (Rigaku D / max-2600PC). Cu Kα rays were used for the test, with a wavelength λ of 0.154056 nm, a voltage of 40 kV, a current of 40 mA, and a scanning range of 2θ of 10–80°. The XRD test results were analyzed using Jade 6 software. Figure 3 The figures show the XRD patterns of lithium manganese oxide obtained in Example 1 and Comparative Example 1. As can be seen from the figures, the materials prepared in Examples 1 and 2 both conform to the Li... 1.6 Mn 1.6 The structure of O4.
[0096] (3) The composition and valence state of the material surface were determined using an ESCALAB 250Xi X-ray photoelectron spectrometer. Figure 4 The figures show XPS test results for lithium manganese oxide obtained in Examples 1, 1, and 5. As can be seen from the figures, Examples 1 and 5, by controlling variables to achieve different micron-sized alumina / water-soluble manganese salt ratios and feed ratios, yielded LAMO with varying Mn content. 3+ The different contents indicate that Al has been successfully doped and entered the LMO lattice. By adjusting the Al / Mn ratio, the Mn content in LAMO can be controlled. 3+ To regulate, specifically, AI 3+ Because the Al-O bond energy formed by its combination with O is greater than the Mn-O bond energy, and the ionic radius is similar to that of Mn... 3+ They are close and have the same valence state, therefore Al 3+ Capable of doping into lithium manganese oxide crystals and partially replacing Mn 3+ This makes the Mn in lithium manganese oxide 3+ The content decreases; thus, Jahn-Teller distortion can be suppressed, reducing manganese dissolution. Compared with Comparative Example 1, the Mn content in Example 1 is lower. 3+ The content is lower, which is due to the different preparation methods. In the process of aging and alkaline hydrolysis, the alumina core of the template agent of this invention gradually reacts with water and alkali, and is discharged or retained through the pores of manganese carbonate. Therefore, the contact of each component is more uniform at the microscopic level.
[0097] (4) The specific surface area and pore size distribution of the material were analyzed using an ASAP2020M specific surface area and microporous adsorption analyzer. Figure 5 The figures show the BET test results of lithium manganese oxide obtained in Example 1 and Comparative Example 1. It can be seen from the figures that the specific surface area of the LAMO prepared in Example 1 is 13.6 m². 2 / g, with an average pore size of 16.5nm; while the LAMO prepared in Comparative Example 1 has a specific surface area of 9.3m². 2 / g, with an average pore size of 9.5nm. Therefore, LAMO prepared using the method of this invention exhibits higher porosity, resulting in higher lithium extraction rate and capacity.
[0098] (4) Lithium extraction performance test
[0099] This invention employs a lithium-rich electrode-lithium-poor electrode system (electrochemical deintercalation / intercalation method) to investigate the lithium extraction performance of samples. Specifically, a lithium-rich electrode is used as the anode, and a lithium-poor electrode as the cathode, separated by an anion exchange membrane. The electrolyte (recovery solution) in the anode chamber is a 0.05 M KCl solution, and the electrolyte (extraction solution) in the cathode chamber is a 0.05 M LiCl solution. The electrode spacing is 4.5 cm, and the voltage is constant at 1 V. After lithium extraction using Ag as the counter electrode, the resulting lithium-poor electrode is used as the cathode to extract Li, and then converted to the anode for further lithium extraction in this system. Samples are taken from the recovery cell after a certain period, and Li is analyzed using ICP-OES. + Calculate the lithium extraction capacity E based on the concentration of Mn ions. Li (mg / g), lithium extraction rate r E (mg·g -1 ·min -1 Manganese dissolution rate E Mn The calculation formulas for indicators such as (mg / g) are shown below:
[0100]
[0101]
[0102]
[0103] In the formula, and These represent the final mass concentration and volume of Li ions in the recovered solution, respectively. and These represent the mass concentration and volume of Li ions sampled at a specific time, where t is the sampling time. Let be the molar concentration of Li+ in the recovered solution at time t. The molar concentration of Li+ in the recovered solution at time 0; and The final mass concentration and volume of Mn ions in the recovered solution. and These represent the mass concentration and volume of Mn ions sampled at a certain time, respectively, where m (in g) is the mass of the lithium ion sieve precursor.
[0104] Meanwhile, by using the lithium-poor electrode material as the cathode for lithium extraction and then as the anode for delithiation in a cycle (one cycle is 120 min), the lithium extraction capacity after 10 cycles was tested, and E was calculated. Li Retention rate is used to evaluate cycle stability.
[0105] The test results are recorded in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] The results in Table 1 show that:
[0110] The specific surface area and average pore size of the LAMO obtained in this invention are related to the particle size of the micron-sized alumina and the mesoporous structure of its surface. The mesoporous structure of the LAMO surface is related to the type of carbonate, the ratio of alumina to manganese salt, and the salt concentration. Specifically, since carbonates dissolve in water to form alkaline or weakly alkaline solutions, alumina undergoes a certain degree of corrosion. Sodium carbonate is more alkaline than sodium bicarbonate, resulting in a stronger ability to form pores on the manganese carbonate surface. Furthermore, the ratio of alumina to manganese salt and the concentration of manganese salt affect the thickness of the hollow sphere shell to some extent, thus influencing the microstructure of the shell. The specific surface area and average pore size of LAMO further affect its lithium extraction performance; specifically, a larger specific surface area results in a higher lithium extraction rate and capacity. The Mn content of LAMO... 3+ The content is related to the amount and effect of aluminum doping, Mn 3+ The lower the content, the lower the manganese loss of LAMO and the better the cycle stability.
[0111] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0112] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0113] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A method for preparing hollow aluminum-doped lithium manganese oxide, characterized in that, The preparation method includes: Alumina, manganese salt and carbonate are mixed to obtain manganese carbonate coated alumina particles; The manganese carbonate-coated alumina particles are subjected to a first calcination to decompose part of the manganese carbonate, resulting in manganese carbonate / Mn2O3-coated alumina particles with porous surfaces. The manganese carbonate / Mn2O3-coated alumina particles were subjected to alkali treatment to obtain the first hollow sphere; The first hollow sphere is subjected to a second calcination to decompose the remaining manganese carbonate, thereby obtaining the second hollow sphere; The second hollow sphere is mixed with a lithium source and then subjected to a third calcination to obtain hollow aluminum-doped lithium manganese oxide.
2. The preparation method according to claim 1, characterized in that, The alumina is a micron-sized powder.
3. The preparation method according to claim 1, characterized in that, The average particle size of the alumina is 1~4μm.
4. The preparation method according to claim 1, characterized in that, The method for mixing alumina, manganese salt and carbonate includes: dispersing alumina in water, adding manganese salt and dissolving it, ultrasonically mixing for 0.5 to 2 hours, adding carbonate dropwise and dissolving it, stirring the reaction for 0.5 to 2 hours after the addition is complete, aging for 8 to 16 hours, and then centrifuging, washing and drying to obtain manganese carbonate coated alumina particles.
5. The preparation method according to claim 1, characterized in that, The amount of manganese salt used should be controlled according to a concentration of 1~1.5 mol / L.
6. The preparation method according to claim 1, characterized in that, The mass ratio of alumina, manganese salt and carbonate is (0.5~1):1.1:
1.
7. The preparation method according to claim 1, characterized in that, The manganese salt includes at least one of manganese chloride, manganese nitrate, manganese acetate, or manganese sulfate.
8. The preparation method according to claim 1, characterized in that, The carbonate includes at least one of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, or ammonium bicarbonate.
9. The preparation method according to claim 1, characterized in that, The heating rate of the first calcination is 1~5℃ / min, the holding temperature is 200~300℃, and the time is 2~3h.
10. The preparation method according to claim 1, characterized in that, The alkaline solution used in the alkaline treatment includes sodium hydroxide or potassium hydroxide.
11. The preparation method according to claim 1, characterized in that, The pH of the alkaline solution used in the alkaline treatment is 9-12.
12. The preparation method according to claim 1, characterized in that, The alkali treatment time is 0.5~1h.
13. The preparation method according to claim 1, characterized in that, The second calcination process involves a heating rate of 1~5℃ / min, a holding temperature of 500~800℃, and a holding time of 4~6h.
14. The preparation method according to claim 1, characterized in that, The lithium source includes lithium hydroxide.
15. The preparation method according to claim 1, characterized in that, The method of mixing the second hollow sphere with the lithium source includes: grinding until there are no obvious particles.
16. The preparation method according to claim 1, characterized in that, The mass ratio of the second hollow sphere to the lithium source is 1:(2~2.2).
17. The preparation method according to claim 1, characterized in that, The third calcination includes calcining at a first temperature and then raising the temperature to a second temperature for further calcination.
18. The preparation method according to claim 17, characterized in that, The first temperature is 100~140℃, and the calcination time at the first temperature is 24~72h.
19. The preparation method according to claim 17, characterized in that, The second temperature is 400~600℃, and the calcination time at the second temperature is 2~6h.
20. The preparation method according to claim 1, characterized in that, The heating rate for the third calcination is 1~5℃ / min.
21. A hollow aluminum-doped lithium manganese oxide, characterized in that, It is obtained using the preparation method according to any one of claims 1-20.
22. The hollow aluminum-doped lithium manganese oxide according to claim 21, characterized in that, The hollow aluminum-doped lithium manganese oxide includes LiAl x Mn 1-x O2 and / or Li 1.6 Al y Mn 1.6-y O4, 0<x<1, 0<y<1.
6.
23. A lithium extraction / deintercalation electrode, characterized in that, Contains the hollow aluminum-doped lithium manganese oxide as described in claim 21 or 22.
24. A lithium extraction device, characterized in that, It contains the lithium extraction and deintercalation electrode as described in claim 23.
Citation Information
Patent Citations
Preparation method for hollow spherical lithium manganate capable of automatically adjusting pore diameters
CN106505191A
Ion-exchange manganese oxide lithium adsorbent using porous structure and method for preparing the same
US20140087071A1
